Vision screening and photorefraction - the relation of refractive errors to strabismus and amblyopia. - Atkinson, J; Braddick, O (1983)
Isotropic photorefraction is a technique well suited for screening infants and young children for refractive errors. The photorefractive measurements have been empirically calibrated against retinoscopic refractions, so errors exceeding selected criteria can be identified in screening and followed up. Such a screening programme is in progress for the population of 6-9 month infants in the City of Cambridge. In 1096 infants screened 5% have been found to have large hypermetropic errors, 1.3% to show a refractive difference between the eyes (anisometropia) and less than 1% to have significant myopia or manifest strabismus. These findings were generally confirmed on retinoscopic examinations. In subsequent follow up of the large hypermetropic errors, most decline with age but a few show little or no change up to age 2 years and some show more change in one eye than the other leading to anisometropia. A trial is underway to examine whether early correction with spectacles can reduce the later incidence of strabismus and amblyopia in hypermetropic infants. Significant astigmatism is found in a large fraction of the infant population; the predominant axis of this astigmatism shows marked and unexplained variations between different locations in England.